Pentingnya Keterampilan Hidup dalam Mewujudkan Ide-Ide Bisnis yang Inovatif - Yurniman Ndruru Susiana Lase; Noverlina Zendrato; Yosia Belo (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
In the ever-evolving landscape of entrepreneurship, life skills play a crucial role in developing and realizing innovative business ideas. This article explores how life skills such as critical thinking, creativity, effective communication, and time management contribute to business innovation. These skills not only assist entrepreneurs in designing and refining new ideas but also support problem-solving, adapting to change, and managing complex challenges. By integrating life skills into the idea development process, entrepreneurs can enhance their competitiveness and create unique and relevant solutions. The article also includes case studies from various successful companies and provides practical recommendations for developing life skills that foster innovation. Overall, life skills are a fundamental foundation in realizing innovative business ideas, influencing both the creative process and the final outcomes of entrepreneurial ventures.